2001
DOI: 10.4319/lo.2001.46.2.0213
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of biotic effects: Zebra mussels (Dreissena polymorpha) influence on water clarity in Saginaw Bay, Lake Huron

Abstract: In this study, Advanced Very High Resolution Radiometer (AVHRR) remote sensing reflectance (R rs ), imagery from 1987-1993 is used to study changes in water clarity before and after zebra mussels (Dreissena polymorpha) were discovered in Saginaw Bay, Lake Huron. Spatial and temporal trends in the data indicate distinct and persistent increases in water clarity in the inner bay after the first large recruitment of zebra mussels in the fall of 1991. The pre-Dreissena imagery show that turbidity in the inner bay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 20 publications
(17 reference statements)
1
31
0
Order By: Relevance
“…It has been suggested that P loading restrictions be relaxed in the lower Laurentian Great Lakes as a means to enhance fisheries yields (e.g., Stockner et al 2000); yet the establishment of abundant benthic filter feeders has shifted the effects of eutrophication (in terms of high algal biomass) towards the nearshore and especially to the littoral zone (Hecky et al 2004;Zhu et al 2006). Dreissenid mussels effectively clear the water column through filterfeeding and, thus, reduce the effects of eutrophication as indicated by water clarity and suspended chlorophyll concentration (e.g., Holland et al 1995, Budd et al 2001. However, we demonstrate how these benthic grazers, by enhancing light availability and possibly by focusing nutrients to the benthos in the littoral, enhances other undesirable effects of eutrophication, specifically, an overabundance of benthic macroalgal biomass.…”
Section: Discussionmentioning
confidence: 70%
“…It has been suggested that P loading restrictions be relaxed in the lower Laurentian Great Lakes as a means to enhance fisheries yields (e.g., Stockner et al 2000); yet the establishment of abundant benthic filter feeders has shifted the effects of eutrophication (in terms of high algal biomass) towards the nearshore and especially to the littoral zone (Hecky et al 2004;Zhu et al 2006). Dreissenid mussels effectively clear the water column through filterfeeding and, thus, reduce the effects of eutrophication as indicated by water clarity and suspended chlorophyll concentration (e.g., Holland et al 1995, Budd et al 2001. However, we demonstrate how these benthic grazers, by enhancing light availability and possibly by focusing nutrients to the benthos in the littoral, enhances other undesirable effects of eutrophication, specifically, an overabundance of benthic macroalgal biomass.…”
Section: Discussionmentioning
confidence: 70%
“…Ecosystem-level functional alteration may be especially pronounced within the state of Alabama, a renowned biodiversity hotspot for freshwater fauna, particularly fishes, crayfish and mollusks (Lydeard and Mayden, 1995). Mussels provide fundamental services such as nutrient cycling (Christian et al, 2008;Jost and Helmuth, 2007), habitat modification (Norkko et al, 2006) and water filtration (Budd et al, 2001). This functional diversity thus supports increased biodiversity within aquatic systems (Donadi et al, 2013;Vaughn et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Efficient suspension feeders, they occur in extremely high densities and cause considerable changes in ecosystem composition/function such as local extirpation of native mussel populations (Strayer et al, 1999), increases in water clarity (Budd et al, 2001) and the removal of microalgae from water columns (Raikow et al, 2004), hence influencing HABs (Reeders et al, 1989;Roditi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%